Health conditions in spousal caregivers of people with dementia and their relationships with stress, caregiving experiences, and social networks: longitudinal findings from the IDEAL programme - Serena Sabatini; Anthony Martyr; Anna Hunt; Laura D. Gamble; Fiona E. Matthews; Jeanette M. Thom; Roy W. Jones; Louise Allan; Martin Knapp; Catherine Quinn; Christina Victor; Claire Pentecost; et al. (BMC Geriatrics, 2024)
Abstract Objectives Longitudinal evidence documenting health conditions in spousal caregivers of people with dementia and whether these influence caregivers’ outcomes is scarce. This study explores type and number of health conditions over two years in caregivers of people with dementia and subgroups based on age, sex, education, hours of care, informant-rated functional ability, neuropsychiatric symptoms, cognition of the person with dementia, and length of diagnosis in the person with dementia. It also explores whether over time the number of health conditions is associated with caregivers’ stress, positive experiences of caregiving, and social networks Methods Longitudinal data from the IDEAL (Improving the experience of Dementia and Enhancing Active Life) cohort were used. Participants comprised spousal caregivers (n = 977) of people with dementia. Self-reported health conditions using the Charlson Comorbidity Index, stress, positive experiences of caregiving, and social network were assessed over two years. Mixed effect models were used Results On average participants had 1.5 health conditions at baseline; increasing to 2.1 conditions over two years. More health conditions were reported by caregivers who were older, had no formal education, provided 10 + hours of care per day, and/or cared for a person with more neuropsychiatric symptoms at baseline. More baseline health conditions were associated with greater stress at baseline but not with stress over time. Over two years, when caregivers’ health conditions increased, their stress increased whereas their social network diminished Discussion Findings highlight that most caregivers have their own health problems which require management to avoid increased stress and shrinking of social networks